Derivation of Breast Cancer Cell Lines Under Physiological (5%) Oxygen Concentrations - Leung, Euphemia Y.; Askarian-Amiri, Marjan E.; Singleton, Dean C.; Ferraro-Peyret, Carole; Joseph, Wayne R.; Finlay, Graeme J.; Broom, Reuben J.; Kakadia, Purvi M.; Bohlander, Stefan K.; Marshall, Elaine; Baguley, Bruce C. (Frontiers in Oncology, 2018)
Background: Most human breast cancer cell lines currently in use were developed and cultured under ambient (20%) oxygen conditions. This is convenient in practical terms, but higher ambient oxygen increases the production of oxygen radicals, potentially modulating numerous signaling pathways and favoring the emergence of oxygen radical-resistant cell lines. We have derived a series of human cancer cell lines under a 5% oxygen atmosphere to mimic physiological conditions and to minimize this stress. Four of these were derived from breast carcinomas and in this report we have investigated the properties of these lines and compared them to those of established breast cancer lines. Methods: Cell lines were characterized in terms of appearance in culture, cellular DNA content, mutation spectrum, hormone receptor status, pathway utilization and drug sensitivity. Results: Three of the four lines (NZBr1, NZBR2 and NZBR4) were triple negative (ER-, PR-, HER2-), with NZBR1 also over-expressing EGFR. NZBR3 was HER2+ and ER+ and also over-expressed EGFR. As determined by protein phosphorylation, NZBR1 showed low AKT pathway utilization while NZBR2 and NZBR4 showed low p70S6K pathway utilization. The lines, in some cases together with some established breast cancer lines, were characterized in terms of sensitivity to the drugs 7-hydroxytamoxifen, doxorubicin, paclitaxel, the PI3K inhibitor BEZ235 and the HER inhibitors lapatinib, afatinib, dacomitinib and ARRY-380. Of particular note was the sensitivity of NZBR2 and NZBR3 to the HER inhibitors. The spectrum of mutations in the NZBR lines was generally similar to that found in commonly used breast cancer cell lines but the mutations EVI2B, LRP1B and PMS2 have not been reported in other breast cancer lines. The availability of these NZBR cell lines adds a further resource for the assessment of genome aberrations and signaling pathway utilization in breast cancer.